Acantholytic invasive squamous cell carcinoma: tumor diameter, invasion depth, grade of differentiation, surgical margins, perineural invasion, recurrence and death rate. (16th January 2017) - Pyne, J. H.; Myint, E.; Barr, E. M.; Clark, S. P.; David, M.; Na, R.
Abstract : Background: Squamous cell carcinoma (SCC) may present with or without the feature of acantholysis. Methods: Investigate invasive acantholytic SCC by microscopic maximum tumor surface diameter, depth of invasion, grade of differentiation, perineural invasion (PNI) and percentage of acantholysis. Assess recurrence following excision. Results: A total of 1658 consecutive invasive SCC cases were examined, comprising 4.9% acantholytic SCC. Median tumor microscopic maximum diameter was 8 mm for acantholytic SCC and 7.3 mm for non‐acantholytic SCC. Median tumor invasion depth was 1.0 mm for acantholytic SCC and 1.5 mm for non‐acantholytic SCC. Well, moderate and poor differentiation were not significantly different between acantholytic SCC and non‐acantholytic SCC. One PNI case was found in 82 acantholytic SCC cases. A total of 77 acantholytic SCC cases were followed up over a median 25 months finding histologic proven recurrence at three acantholytic SCC excision sites. Conclusions: Acantholytic SCC were more likely to be located on head sites with less median depth than non‐acantholytic SCC. Increasing percentage of acantholysis within acantholytic SCC was not associated with a shift towards poor differentiation. Histologic margins of 1.2 mm may adequately excise small acantholytic SCC. No recorded deaths, low PNI and low recurrence rates suggests acantholytic SCC is low‐risk.